Opportunities and challenges in combining immunotherapy and radiotherapy in head and neck cancers. (April 2022) - Wong, Kenneth C.W.; Johnson, David; Hui, Edwin P.; Lam, Rachel C.T.; Ma, Brigette B.Y.; Chan, Anthony T.C.
Highlights: Pre-clinical data showed that radiation and immunotherapy have synergistic effects. Virus-induced cancers have unique immune landscapes which could be exploited. Many trials are investigating the combination of radiation (RT) and immunotherapy. Trials have so far largely failed to show the additional benefits of immunotherapy. More work is needed to define the optimal RT dose/ timing and the use of biomarkers. Abstract: Locally advanced and recurrent/ metastatic (R/M) head and neck cancers have poor prognosis generally. Radiotherapy (RT) is known to have multiple immunomodulatory effects, and various immune checkpoint inhibitors (ICIs) have been shown to be efficacious in the R/M setting in recent years. Hence, it is logical to combine RT and ICIs to improve the outlook for such patients, especially in view of the promising pre-clinical data on this novel combination. In this review, we highlighted the key mechanisms underlying the immunostimulatory and immunoinhibitory effects of RT, with a view to suggesting strategies to overcome radioresistance. We also discussed how the unique immune landscapes of virus-induced cancers, namely Epstein-Barr virus-induced nasopharyngeal carcinoma and human papillomavirus-mediated oropharyngeal cancer, could be exploited with ICIs. The landmark clinical trials in both the locally advanced and R/M settings were reviewed, and these trials showed that the combination of RT and ICIs is generally well tolerated. The potential reasons behind the largely negative results of these studies were also explored, focusing on various parameters including dose fractionation, sequencing, irradiated volume and the use of predictive biomarkers.